Lethal toxicity of monocrotophos on the juveniles of rohu and mrigal - Sulekha, B T; Anna Mercy, T V; Nair, J R (Indian Journal of Fisheries, 2011)
The 96 hour LC50 value of monocrotophos - a widely used organophosphatepesticide in the paddy fields of Kerala on the juveniles of rohu and mrigal arefound to be 46.34 and 42.33 ppm respectively. It is seen that rohu is more resistantthan mrigal. Both rohu and mrigal can be recommended as potential candidatesfor culture practices in the paddy-cum-fish culture systems, as they show highpesticide tolerance. But further studies are required on the residue accumulationand depuration in the body of these fishes